The Effect Of Product Quality And Price On Customer Satisfaction at Love Tempe, Sempali Village - Yusta Yuniati Gulo; Dwi Pertiwi Anggraini; Ronda Deli Sianturi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
This study aims to examine the influence of product quality and price on customer satisfaction at Love Tempe in Desa Sempali. A quantitative approach was applied, using multiple linear regression as the analytical method. A total of 50 respondents were selected through purposive sampling, targeting customers who had purchased Love Tempe products more than once. Data were collected using a Likert-scale questionnaire and analyzed with SPSS version 25. The findings indicate that product quality has a positive and significant effect on customer satisfaction. Price also shows a positive and significant influence on customer satisfaction. Together, both variables contribute 68.4 percent to the level of customer satisfaction. These results highlight the importance of maintaining product quality and setting prices that reflect customer perceptions of value. The study provides insights that can help business owners improve product consistency and develop more effective pricing strategies